Pengaruh Pengalaman, Motivasi Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai Di Kantor Kementerian Agama Kabupaten Cilacap - Rizal Fauzi (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
Employee performance in an organization cannot be separated from experience, motivation and leadership style. The Ministry of Religion of Cilacap Regency really needs effective leaders, who have the ability to influence the behavior of their subordinates in increasing motivation in order to increase their work experience, so that they can improve the performance of their employees to achieve organizational goals. This research aims to determine the influence of experience on employee performance, the influence of motivation on employee performance, the influence of leadership style on performance and the influence of experience, motivation and leadership style together on employee performance at the Cilacap Regency Ministry of Religion Office. The research method uses quantitative descriptive methods. Meanwhile, the data collection technique uses a questionnaire, and data analysis uses multiple linear regression. The research results show that there is an influence between experience, motivation and leadership style together on employee performance at the Cilacap Regency Ministry of Religion Office. This means that the more employee work experience and the higher the employee's work motivation and the better the leadership, the better the employee's performance at the Cilacap Regency Ministry of Religion Office. Vice versa.